Playing Hare and Tortoise: The FigarOS Kernel for Fine-Grained System-Level Energy Optimizations - Hönig, Timo; Eibel, Christopher; Herzog, Benedict; Janker, Heiko; Wägemann, Peter; Schröder-Preikschat, Wolfgang (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
Energy has emerged to be the most important resource for computing systems. Despite the exceptional importance of energy, reducing its demand at application and system level remains a challenging task for programmers and engineers. This is aggravated by the fact that traditional energy-saving approaches are not only error-prone but even lead to adverse consequences (i.e. increased energy consumption). To address this concern, we present the FigarOS operating system for fine-grained system-level energy optimizations. The evaluation of our FigarOS implementation shows that the operating system lowers the energy consumption of processes by up to 2.9 x.